2016
DOI: 10.1002/cam4.730
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a gap junction protein, connexin43, in a large panel of human gliomas: new insights

Abstract: Precise diagnosis of low and high grades of brain tumors permits determining therapeutical strategies. So far, diagnosis and prognosis of gliomas were based on histological and genetic criteria which need being completed by a panel of molecular markers. Highly distributed in brain, gap junction proteins, connexins, could be considered as markers of glioma progression as previous studies indicated that expression of a connexin type, connexin43 (Cx43), is inversely correlated to tumor grading. However, this assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…While these data are consistent with the hypothesis that Cx43 is a tumor suppressor, ongoing research has revealed novel functions of Cx43 in GBM disease progression and therapeutic responses. In three studies using a much larger cohort of GBM patients (16, 37, and 74 specimens, respectively), percentages of patients expressing Cx43 were 62.2%, 62.5%, and 77%, respectively [13,21 • ,22]. A report by Cottin and colleagues further determined that more than 10% of GBM tumors (9 out of 74) displayed strong Cx43 immunostaining [22].…”
Section: Connexin43 Expression In Malignant Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…While these data are consistent with the hypothesis that Cx43 is a tumor suppressor, ongoing research has revealed novel functions of Cx43 in GBM disease progression and therapeutic responses. In three studies using a much larger cohort of GBM patients (16, 37, and 74 specimens, respectively), percentages of patients expressing Cx43 were 62.2%, 62.5%, and 77%, respectively [13,21 • ,22]. A report by Cottin and colleagues further determined that more than 10% of GBM tumors (9 out of 74) displayed strong Cx43 immunostaining [22].…”
Section: Connexin43 Expression In Malignant Gliomamentioning
confidence: 99%
“…Furthermore, characterization of 10 GSCs lines derived from established cell lines, xenografts, and freshly dissected patient tumor tissues indicated variation in self-renewal capabilities, gene expression profiles, and chemotherapeutic susceptibility [16 •• ]. Recent reports also emphasize the importance of Cx43 subcellular localization and how these findings may translate to recently reported in vitro findings [21 • ]. Given that expression and localization of Cx43 in the nucleus and cytoplasm has been shown to reduce the growth of human GBM cells without a corresponding change in GJIC [19], further investigation into the molecular interactions and signaling pathways that may be impacted by Cx43 subcellular localization and what roles these may play in glioma progression and chemotherapeutic resistance is warranted.…”
Section: Connexin43 Expression In Malignant Gliomamentioning
confidence: 99%
“…It is also decreased in the majority of GBM, where the expression of Cx43 protein is insignificant (12,26,27). However, Crespin et al (28) did not share this point of view. First, in spite of the modest inverse association between tumor grade and Cx43 expression, over half of glioblastomas still express Cx43.…”
Section: Expression Of Cx43 and Glioma Gradementioning
confidence: 97%
“…[3][4][5] Cucurbitacins, a class of tetracyclic triterpenoids with medicinal properties in Cucurbitaceae, are extracted from the climbing stems of Cucumis melo L. 6 Cucurbitacins have been widely used in inhibition of cancer cell progression as medicinal herbs throughout Asia. 1 However, the chemotherapy for brain cancer remains obscure.…”
Section: Introductionmentioning
confidence: 99%